Osteoporosis: An ignored complication of CVID - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (WILEY, 2011)
Background: Multiple factors in common variable immunodeficiency (CVID) might interfere with optimal growth and maturation and potentially compromise bone health. Methods: We aimed to evaluate bone mineral density (BMD) of patients with CVID using dual energy X-ray absorptiometry (DEXA) and investigate risk factors associated with decreased bone density. Results: Twenty-two patients were included (M: 16, F: 6) with a mean age of 15.6 +/- 9.0 yr. DEXA revealed osteopenia in 6/22 (27.3%) and osteoporosis in 9/22 (40.9%) at lumbar spine and osteopenia in 7/19 (37%) and osteoporosis in 3/19 (16%) at femoral neck sites. The age of subjects with osteoporosis was significantly higher than those without (21.6 +/- 8.0 vs. 9.0 +/- 5.7 yr; p < 0.0001). BMD z-scores were significantly lower in patients with bronchiectasis compared with those without (p = 0.03). Patients with osteoporosis at femoral neck site had lower forced expiratory volume in 1 s (FEV1) (p = 0.024), FEV1/forced vital capacity (FVC) (p < 0.0001), PEF (p = 0.008), and FEF 25-75 (p = 0.013) values compared with the patients with normal BMD z-scores. Low serum 25(OH) vitamin D levels were detected in 13/22 patients and low dietary calcium intake in 17/22 patients. BMD z-scores at femoral neck were lower in patients with low B-cell percentage (p = 0.03). BMD z-score at lumbar spine was correlated with folate (r = +0.63, p = 0.004) and serum immunoglobulin G levels (r = +0.430, p = 0.04). Conclusion: Osteoporosis appeared as an emerging health problem of patients with CVID, the risk increasing with older age and poorer lung function. Nutritional, biochemical, and immunologic factors appeared to take part in decreased BMD. Insight into the mechanisms of osteoporosis in CVID is crucial to develop preventive strategies.
Keywords: common variable immunodeficiency; osteoporosis; chronic lung disease; folate; BONE-MINERAL DENSITY; COMMON VARIABLE IMMUNODEFICIENCY; CYSTIC-FIBROSIS; PEDIATRIC-PATIENTS; VITAMIN-D; WOMEN; HOMOCYSTEINE; METABOLISM; INFECTION; CHILDREN